Interpersonal, Leadership, and Supervisory Skills of Public School Heads - Trongco, Goldie P.; Benolirao, Eingilbert C. (Future Science / FSH-PH Publications, 2023)
This study determined the level of competency of the Elementary School Heads in the District of Sibonga, along with the aspects of interpersonal, leadership, and supervisory skills during the school year 2020-2021 a basis for the management training framework. The areas of concern included the perceived level of competency in terms of interpersonal, leadership, and supervisory skills; the significant difference in the perception of the respondent groups of the three variables; the participants’ perspectives towards the three variables; and the management training framework. The result of the study showed that the respondents showed the same level of competency. Most of them have maintained a competent level of perception. Based on the result, respondents showed the same level of perception as to the different variables presented and no significant difference between them. It can be concluded that the passion and enthusiasm of our teachers and school heads are still maintained and even doubled due to the sudden change in learning approach. It is recommended that there is a need to assess the leadership style and situational favorableness of our teachers and school heads. With that, the Management Training Framework is being proposed.